SEQUENCE, STRUCTURE, AND NP-COMPLETE PROBLEMS. - Carifio, James (Journal of Research in Science Teaching, 1979)
The article comments on a paper by R. T. White about the nine-step process for developing a validated learning hierarchy for any given intellectual skill. He points out the that White's paper is implying a suggestion that such process should be used by professional curriculum developers in designing classroom instructional programs in science education. He argues that the author's opinion in his article does not vitiate the fact that the learning hierarchy model is a potentially efficient and easy to apply strategy for developing relatively effective instructional sequences, if it is viewed for a development strategy of working.